Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Let's take this problem step-by-step:
Note:
'-- (1), -- (2), etc.' are equation markers used to show steps
First step, isolate all the variables to one side and constant to the other
[tex]3x + 2y = 8--(1)\\3x-y=-3--(2)[/tex]
Second step: (1) - (2)
[tex](1) - (2)\\3x + 2y-(3x-y)=8-(-3)\\2y + y=11\\3y = 11\\y = \frac{11}{3} --(3)[/tex]
Third step: Plug (3)'s value of y into (2)
[tex](3)_.into_.(2)\\3x -\frac{11}{3} = -3\\3x = \frac{11}{3}-3\\ 3x = \frac{11-9}{3} \\3x = \frac{2}{3} \\x=\frac{2}{9}[/tex]
Answer: x = 2/9, y = 11/3
Hope that helps!
#LearnwithBrainly
Answer:
3x+ 2y=8 ⇒ ( 1 )
3x+3=y ⇒ ( 2 )
First, let us take the equation (1).
We can replace y with ( 3x + 3 ).
Solving the below expression let us find the value of x.
[tex]3x + 2y = 8\\3x + 2 ( 3x + 3 ) = 8\\3x + 6x + 6 = 8\\9x + 6 = 8\\9x = 8 - 6\\9x = 2\\x = \frac{2}{9}[/tex]
And now let us take equation ( 2) to find the value of y.
For that let us replace x with 2/9.
Let us find it now.
[tex]3x+3=y\\\\3*\frac{2}{9} +3=y\\ \\\frac{6}{9} +3=y\\ \\\frac{6}{9} +\frac{3}{1} =y\\\\\frac{6}{9} +\frac{3*9}{1*9} =y\\\\\frac{6}{9} +\frac{3*9}{1*9} =y\\\\\frac{6}{9} +\frac{27}{9} =y\\\\\frac{33}{9} =y\\\\\frac{11}{3} = y[/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.